Hubungan Antara Kadar Neutrophil-to-Lymphocyte Ratio dengan Kejadian Hiperemesis Gravidarum pada Ibu Hamil - Ghanisya Ailsa Nathaniela; Yulice Soraya Nur Intan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Previous studies have reported that inflammatory levels in pregnant women with hyperemesis gravidarum tend to be higher than those in normal pregnancies. This study aimed to determine the association between Neutrophil-to-Lymphocyte Ratio (NLR) levels and the incidence of hyperemesis gravidarum among pregnant women at Dr. Amino Gondohutomo Regional Mental Hospital during the period 2022–2025. This study employed an analytic observational design with a case-control approach and consecutive sampling technique. A total of 92 subjects were included, consisting of 46 pregnant women with hyperemesis gravidarum and 46 pregnant women without hyperemesis gravidarum. The study utilized medical record data from 2022 to 2025. Data were analyzed using quantitative statistical methods, including descriptive analysis, Shapiro–Wilk normality test, and Chi-Square test. Elevated NLR levels were more frequently observed in the hyperemesis gravidarum group (29 cases, 31.5%) compared to the non-hyperemesis gravidarum group (15 cases, 16.3%) (p=0.003, OR=3.5, 95% CI=1.493–8.326). This study demonstrates a significant association between NLR as an inflammatory indicator and the incidence of hyperemesis gravidarum at Dr. Amino Gondohutomo Regional Mental Hospital, Semarang..